The Influence of Ethical Work Climates on Public Sector Supplier Selection Decisions - Eyo Emmanuel, Essien (British Journal of Marketing Studies, 2018)
This study examined the relationship between ethical work climates (EWCs) and supplier selection decisions (SSD), and the moderating roles of party politics and personal values on this relationship. A total of 600 senior level personnel from 40 Nigerian public sector organizations were surveyed. Results show that both high and low levels of external political pressures significantly reduce the perception that organisational SSDs are ruled-based and pro-social in nature. Furthermore, regardless of the level of perception of instrumental personal values by employees, instrumental ethical climates significantly determine SSDs; principled/cosmopolitan climate and benevolent/cosmopolitan climate only become significant perceptible determinants when there is less room for the accommodation of personal goals during SSD processes. We conclude that the EWC dimensions do really reflect the Nigerian public sector SSD outcomes. Important implications for theory and practice are also presented.